2003
DOI: 10.1139/w03-082
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characteristics and population genetics ofEnterococcus faecaliscultured from patients in Tehran during 2000–2001

Abstract: Conventional bacteriology techniques were used to identify enterococci isolates cultured from patients at different hospitals in Tehran during 2000-2001. The identification was confirmed using species-specific PCR targeting the D-alanyl-D-alanine ligase gene. A total of 59 isolates of Enterococcus faecalis were identified. The rates of resistance to different antibiotics were in the following order: penicillin 84%, ciprofloxacin 42%, high-level gentamicin 30%, nitrofurantoin 14%, imipenem 4%, and chloramphenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In the past 4 decades in Iran, aminoglycosides, particularly gentamicin, have been used broadly in the treatment of infections, which can be one of the causes of high prevalence of HLGR isolates in Iran's hospitals (25). In our study, high-level resistance to gentamicin was observed in 31 % of isolated enterococci.…”
Section: Discussionsupporting
confidence: 46%
“…In the past 4 decades in Iran, aminoglycosides, particularly gentamicin, have been used broadly in the treatment of infections, which can be one of the causes of high prevalence of HLGR isolates in Iran's hospitals (25). In our study, high-level resistance to gentamicin was observed in 31 % of isolated enterococci.…”
Section: Discussionsupporting
confidence: 46%
“…In this study, a total of 120 Enterococcal isolates were investigated. Various studies in Iran suggests that this bacterium is endemic in hospitals and has an important role in hospital infections (11,12). In a study in Babol, the frequency of isolation for E. faecalis and E. faecium were reported as 63% and 33%, respectively (13 (13).…”
Section: Discussionmentioning
confidence: 99%
“…No information is available on HLGR strains of E. faecalis in Iran or on the role of plasmids encoding this resistance. We previously used multilocus enzyme electrophoresis (MEE) to study the population genetics of E. faecalis in Iran and showed that the Iranian population of this species is not clonal (Feizabadi et al 2003). We also identified a considerable number of isolates that were highly resistant to aminoglycosides, which suggested the possible existence of successful HLGR strains.…”
mentioning
confidence: 99%
“…E. faecalis ATCC 29212 and a Danish isolate with an HLGR phenotype (kindly provided by Frank Aarestrup) were used as controls, and E. faecalis JH2-2 was used as the recipient in conjugation experiments. All isolates were identified to species level using standard bacteriological methods (Manero and Blanch 1999), and the results were confirmed by PCR (Feizabadi et al 2003). Isolates with HLGR phenotype were recognized using disks containing 120 µg gentamicin (Antalek et al 1995) and were confirmed by the macro-broth dilution method (Barisic and Punda-Polic 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation